Recent Progress of Nanoscale Metal-Organic Frameworks in Cancer Theranostics and the Challenges of Their Clinical Application - Sun W (Dove Medical Press, 2020)
Wenjie Sun,1 Shuying Li,1 Guiliang Tang,1 Yuan Luo,1 Shijing Ma,1 Shaoxing Sun,1 Jiangbo Ren,2 Yan Gong,2 Conghua Xie1,3,4 1Department of Radiation and Medical Oncology, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 2Department of Biological Repositories, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 3Hubei Key Laboratory of Tumor Biological Behaviors, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 4Hubei Cancer Clinical Study Center, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of ChinaCorrespondence: Conghua Xie; Yan GongZhongnan Hospital of Wuhan University, 169 Donghu Road, Wuhan, Hubei 430071, People’s Republic of ChinaTel +86-27-67812607; +86-27-67871471Fax +86-27-67812892; +86-27-67811461Email chxie_65@whu.edu.cn; yan.gong@whu.edu.cnAbstract: The growing incidence of cancer raises an urgent need to develop effective diagnostic and therapeutic strategies. With the rapid development of nanomedicine, nanoscale metal-organic frameworks (NMOFs) presented promising potential in various biomedical applications in the last 2 decades, especially in cancer theranostics. Due to the unique features of NMOFs, including structural diversities, enormous porosity, multifunctionality and biocompatibility, they have been widely used to deliver imaging contrast agents and therapeutic drugs. Moreover, multiple types of contrast agents, anti-cancer drugs and targeting ligands could be co-delivered through one single NMOF to enable combination therapy. Co-delivering system using NMOFs helped to avoid multidrug resistance, to reduce adverse effects, to achieve imaging-guided precise therapy and to enhance anti-cancer efficacy. This review summarized the recent research advances on the application of NMOFs in biomedical imaging and cancer treatments in the last few years. The current challenges that impeding their translation to clinical practices and the perspectives for their future applications were also highlighted and discussed.Keywords: nanomedicine, theranostic platform, biomedical imaging, combination therapy, clinical translation